Performance Of Aqueous Impregnated Resin System For Purification Of Bacteriocin From Lactobacillus Bulgaricus Ftdc 1211 - Aziz, Nur Fazrin Husna Abdul (2020)
Conventional purification method of bacteriocins often requires laborious series of complicated procedures, high cost and low yield. Recent single purification step using aqueous two-phase system has long settling time, low interfacial tension and small density difference. To overcome this problem, in our study, the aqueous impregnated resins system (AIRS) was proposed and developed to purify bacteriocin-like inhibitory substances produced by Lactobacillus bulgaricus FTDC 1211 which exhibited antimicrobial activity against Staphylococcus aureus in our study. In AIRS, hydrophobic polymer phase was impregnated into resins and hydrophilic aqueous phase acts as extraction solution to separate the bacteriocin in cell-free crude supernatant. The bacteriocin was then extracted in the polymer impregnated resins. Before conducting bacteriocin purification experiment, the performance of AIRS in extracting biological product was investigated using bovine serum albumin (BSA) as protein model. The impregnation stability of the hydrophobic polymer in three different types of resin (Amberlite XAD4, VitraPor glass pellets 4.0 mm and 8.0 mm) was investigated. Amberlite XAD4 resins showed the most stable impregnation of PEG with less than 1% (w/w) of leaching factor. A smooth surface on PEG impregnated Amberlite XAD4 was observed under scanning electron microscopy.